Constructing Ambient Intelligence AmI 2008 Workshops, Nuremberg, Germany 19-22, 2008. Revised Papers - Gerhũser, Heinz.; Hupp, J<U+00fc>rgen.; Efstratiou, Christos.; Heppner, Janina. (Communications in Computer and Information Science, 2009)
This book constitutes the refereed proceedings of the workshops of the Second European Conference on Ambient Intelligence, AmI 2008, held in Nuremberg, Germany, in November 2008. The volume includes the workshops: Smart Design for Human Performance, Smart Products: Building Blocks of Ambient Intelligence, Intelligent Objects for the Internet of Things, Social Intelligence for Well-Being and Care, When Ambient Intelligence meets Web 2.0: Wiki-City - A City interacts with its citizen; as well as the project workshops: SOPRANO, PERSONA, Netcarity and MPOWER, Conjoint Workshop on Ambient-Assisted Living, Architectures and platforms for AMI Ambient Assisted Living" and "Personal Health" - between Paragdigms, Projects and Products, Capturing Ambient Assisted Living Needs.